EXAMINING THE IMPACT OF UPRIGHT TIME ON FRAILTY CHANGES IN ACUTE CARE. (11th November 2018) - Theou, O; Kehler, D; Mallery, K; MacLean, M; Rockwood, K
Abstract: The objective of this study was to determine the association between duration and frequency of upright time with frailty changes in acute care. One-hundred and thirty patients were recruited within 48-hr of admission to acute care. Frailty was measured with a 30-item frailty index at admission and at 2 weeks or at hospital discharge in those with a hospital length of stay less than 2 weeks. The frequency and duration of bouts of upright time were measured daily using ActivPAL inclinometers. Ninety-two participants (mean age 82.1 ± 8.0; 57.7% female) had complete ActivPAL and frailty data. Median upright time/day during awake hours (6AM-10PM) was 44.7 (IQR: 24.9–63.0) minutes. The frequency of upright bouts/day during awake hours was 19.2 (IQR: 9.5–30) and the median upright bout duration was 2.8 (IQR: 1.8–4.2) minutes. The frequency of upright bouts/day was independently associated with lower frailty levels at hospital discharge/2weeks (β-coefficient: -0.0022, 95% CI: -0.0001 to -0.004; p=0.04) after adjusting for age, sex, and frailty at admission; whereas, upright bout duration was not. Seventy patients (76%) accumulated daily ≥5 bouts/day lasting at least 2 minutes. Those patients had significantly lower frailty scores at 2 weeks/discharge (β-coefficient: -0.086, 95% CI: -0.014 to -0.157; p=0.01) and a shorter hospital length of stay (12 days; 95% CI: 0.270–24.11 days; p=0.05) compared to those who did not meet these criteria. Reducing bed rest with upright time in acute care is linked to lower frailty levels at hospital discharge. A clinical trial is needed to confirm these findings.